Media Literacy and Digital Privacy Management among Indonesian University Students on Social Media - Nazhifah; Aidil Haris; Fitria Mayasari; Dony Rano Virdaus; Andhita Risko Faristiana (INJECT (Interdisciplinary Journal of Communication), 2026)
This study aims to determine how proficient students at the University of Muhammadiyah Riau are in using technology and managing the privacy of their communication on social media, considering online crimes and potential misuse of personal data. Using a descriptive purposive sampling technique. The results show that students possess good digital literacy in maintaining communication privacy and security on social media. They demonstrate awareness of digital, ethical, security, and cultural components that support responsible digital behavior, indicating that these literacy dimensions are effectively implemented in managing students’ privacy and digital footprint.